NRT2.1 C‐terminus phosphorylation prevents root high affinity nitrate uptake activity in Arabidopsis thaliana. Issue 3 (12th September 2020) - Jacquot, Aurore; Chaput, Valentin; Mauries, Adeline; Li, Zhi; Tillard, Pascal; Fizames, Cécile; Bonillo, Pauline; Bellegarde, Fanny; Laugier, Edith; Santoni, Véronique; Hem, Sonia; Martin, Antoine; et al.
Summary: In Arabidopsis thaliana, NRT2.1 codes for a main component of the root nitrate high‐affinity transport system. Previous studies revealed that post‐translational regulation of NRT2.1 plays an important role in the control of root nitrate uptake and that one mechanism could correspond to NRT2.1 C‐terminus processing. To further investigate this hypothesis, we produced transgenic plants with truncated forms of NRT2.1. This revealed an essential sequence for NRT2.1 activity, located between the residues 494 and 513. Using a phospho‐proteomic approach, we found that this sequence contains one phosphorylation site, at serine 501, which can inactivate NRT2.1 function when mimicking the constitutive phosphorylation of this residue in transgenic plants. This phenotype could neither be explained by changes in abundance of NRT2.1 and NAR2.1, a partner protein of NRT2.1, nor by a lack of interaction between these two proteins. Finally, the relative level of serine 501 phosphorylation was found to be increased by ammonium nitrate in wild‐type plants, leading to the inactivation of NRT2.1 and to a decrease in high affinity nitrate transport into roots. Altogether, these observations reveal a new and essential mechanism for the regulation of NRT2.1 activity. Abstract : See also the Commentary on this article by Rahikainen & Kangasjärvi (2020), 228 : 802–804 .